Translating the cultural and socio-political dimensions of Huaxiaosheng (Chinese-educated Singaporeans) : a case study of Youli Fenzi - Ho, Danyuan (2019)
Huaxiaosheng, or Chinese-educated Singaporeans, is a category of people educated in Mandarin and socialised in Chinese-medium schools from secondary school levels and above. With the ascendancy of English in Singapore, huaxiaosheng faced social difficulties due to their lack of English proficiency and felt humiliated that Chinese-ness has become associated with “communism, backwardness and obsolescence”. Such sentiments are often reflected in the literary works of Singapore Chinese authors who felt anxious over the decline of Chinese language and culture, as well as a sense of loss over social transformation. Using the short novel Youli Fenzi as a case study, this thesis examined the consideration of translating huaxiaosheng as a cultural category, focusing on their cultural and socio-political dimensions. To effectively translate the source text, the translator should have an intimate understanding of the source culture, as well as the social-political contexts that define the cultural identity of huaxiaosheng. Likewise, the reception of the target readers towards the translated text should be considered to ensure the effective transfer of ideological message in the source text. Various techniques were used to explicate the socio-political references deliberately obfuscated in the novel so as to bridge the knowledge gaps of target readers of a different socio-historical context. The translation process reflected the ideology of the translator through foreignisation to preserve the cultural dimensions of huaxiaosheng and the translation decisions to retain the message of cultural and linguistic marginalisation of the source text. By showing how translation can be used to reflect the anxiety of the writers and the community represented by Singapore Chinese literature, this thesis recommends translator activist to use literary translation to promote issues pertinent to particular linguistic or cultural groups. Ultimately, this translation, as an advocacy piece, hopes to improve the cultural image of huaxiaosheng among the English readers.